A novel arithmetic sequence pattern reconfiguration technique for line loss reduction of photovoltaic array under non-uniform irradiance. (10th January 2022) - Anjum, Shahroz; Mukherjee, V.
Abstract: Partial shading causes unwanted impact on the output produced by the photovoltaic arrays. This occurs because some modules in the array are covered by shade while others are not in the same array. As a result of this phenomenon, multiple peaks arise in the P–V characteristics of the photovoltaic array along with sudden and severe row current changes. Both factors impede the array performance. This manuscript presents a novel static reconfiguration technique ( i.e., arithmetic sequence pattern configuration) and verifies it using an experimental work bench to reduce the shading effect on the array. This novel approach reconfigures the conventional total cross tied array in the arithmetic sequence pattern that helps to reduce the shading effect on a specific point and distributes it evenly across all the rows and increases the overall energy output. This manuscript examines and compares different techniques such as SuDoKu, futoshiki SuDoKu, improved SuDoKu, skyscraper SuDoKu and modified SuDoKu interconnections based on various factors like fill factor, mismatch power loss, efficiency, and global maximum power points. Finally, the present work concludes that the suggested arithmetic sequence pattern topology effectively reduces the shading effect and wiring losses. It provides better power output in reference to the other topologies. The proposed topology provides a maximum reduction of 37.98% in wire length as compared to skyscraper SuDoKu and minimum mismatch power loss of 594.8 W lesser as compared to the other configurations. Graphical abstract: Image 1 Highlights: Novel arithmetic sequence pattern (ASP) is proposed to reduce the partial shading effect. ASP is compared with SuDoKu, FSS, IMPS, MS and SKYCS through five case studies. Simulation and experimental results confirm the superior performance of the ASP. ASP outperforms competing topologies with 0%–37.98% reduction in wiring length. Exhibits lowest mismatch loss with 179.5 W–726.6 W reductions for all the case studies.